2003
DOI: 10.1021/ic0345166
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Effect on Reversible Conversion between Copper(I) and Bis(μ-oxo)dicopper(III) Complex with a Sterically Hindered Tetradentate Tripodal Ligand and Monooxygenase Activity of Bis(μ-oxo)dicopper(III) Complex

Abstract: A new sterically hindered tetradentate tripodal ligand (Me2-etpy) and its labeled analogue having deuterated methylene groups (d4-Me2-etpy) were synthesized, where Me2-etpy is bis(6-methyl-2-pyridylmethyl)(2-pyridylethyl)amine. Copper(I) complexes [Cu(Me2-etpy or d4-Me2-etpy)]+ (1 and 1-d4, respectively) reacted with dioxygen at -80 degrees C in acetone to give bis(mu-oxo)dicopper(III) complexes [Cu2(O)2(Me2-etpy or d4-Me2-etpy)2](2+) (1-oxo and 1-d4-oxo, respectively), the latter of which was crystallographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…The cores are planar for all O species studied to date (Table S3). 21-23,36,69-74 A slight improvement in the bond lengths of the Cu 2 O 2 core (Cu ⋯ Cu, O ⋯ O, and Cu–O) is observed with 20-38% Hartree–Fock mixing. The experimental and calculated difference in the Cu ⋯ Cu and O ⋯ O distances along the series of differing HF mixing are within 0.05 Å and 0.03 Å, respectively, and smaller than the difference observed for the P complexes.…”
Section: Results and Analysismentioning
confidence: 97%
“…The cores are planar for all O species studied to date (Table S3). 21-23,36,69-74 A slight improvement in the bond lengths of the Cu 2 O 2 core (Cu ⋯ Cu, O ⋯ O, and Cu–O) is observed with 20-38% Hartree–Fock mixing. The experimental and calculated difference in the Cu ⋯ Cu and O ⋯ O distances along the series of differing HF mixing are within 0.05 Å and 0.03 Å, respectively, and smaller than the difference observed for the P complexes.…”
Section: Results and Analysismentioning
confidence: 97%
“…18,19 Although no X-ray crystal structure has yet been obtained for oxytyrosinase, spectral data for oxyhemocyanin and oxytyrosinase are sufficiently similar that there is little doubt that the resting state of oxytyrosinase also involves a side-on µ-η 2 :η 2 peroxo with five or six histidine ligands. 6 However, Tolman and co-workers, 11,13,17,20,21 and later others, [22][23][24][25][26] have demonstrated that in select instances the relative energies of isomeric µ-η 2 :η 2 peroxo and bis(µ-oxo) complexes can be sufficiently close to one another, and the barrier to their interconversion sufficiently low, that the two species may be in rapid equilibrium with one another; theoretical studies have rationalized many of the electronic structural details governing this phenomenon. [27][28][29][30][31][32][33][34] This observation potentially complicates mechanistic analysis in model systems and, by extension, oxytyrosinase, because the kinetics for systems characterized by a rapid preequilibrium can be indistinguishable from systems involving only a single reactant.…”
Section: Introductionmentioning
confidence: 99%
“…113.86 (8) between the phenolic protons and the amino nitrogen atoms (H1A · · · N3 1.961 Å ) were observed. The Cu · · · Cu separation was determined to be 2.9106(8) Å .…”
Section: Methodsmentioning
confidence: 97%